Proof of an Outer Membrane Target of the Efflux Inhibitor Phe-Arg-β-Naphthylamide from Random Mutagenesis - Sabine Schuster; Jürgen A. Bohnert; Martina Vavra; John W. Rossen; Winfried V. Kern (Molecules, 2019)
Phe-Arg-β-naphthylamide (PAβN) has been characterized as an efflux pump inhibitor (EPI) acting on the major multidrug resistance efflux transporters of Gram-negative bacteria, such as AcrB in Eschericha coli. In the present study, in vitro random mutagenesis was used to evolve resistance to the sensitizing activity of PAβN with the aim of elucidating its mechanism of action. A strain was obtained that was phenotypically similar to a previously reported mutant from a serial selection approach that had no efflux-associated mutations. We could confirm that acrB mutations in the new mutant were unrelated to PAβN resistance. The next-generation sequencing of the two mutants revealed loss-of-function mutations in lpxM. An engineered lpxM knockout strain showed up to 16-fold decreased PAβN activity with large lipophilic drugs, while its efflux capacity, as well as the efficacy of other EPIs, remained unchanged. LpxM is responsible for the last acylation step in lipopolysaccharide (LPS) synthesis, and lpxM deficiency has been shown to result in penta-acylated instead of hexa-acylated lipid A. Modeling the two lipid A types revealed steric conformational changes due to underacylation. The findings provide evidence of a target site of PAβN in the LPS layer, and prove membrane activity contributing to its drug-sensitizing potency.